Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Certainly! To determine the solution for the quadratic inequality [tex]\(x^2 - 3x - 28 \geq 0\)[/tex], we follow these steps:
1. Identify the quadratic equation: We start with the quadratic expression given in the inequality:
[tex]\[ x^2 - 3x - 28 \geq 0. \][/tex]
2. Find the roots of the quadratic equation: The next step is to find the roots of the quadratic equation by setting it equal to zero:
[tex]\[ x^2 - 3x - 28 = 0. \][/tex]
To factorize this equation, we look for two numbers that multiply to [tex]\(-28\)[/tex] and add up to [tex]\(-3\)[/tex]. The numbers [tex]\(-7\)[/tex] and [tex]\(4\)[/tex] satisfy these conditions:
[tex]\[ (x - 7)(x + 4) = 0. \][/tex]
So, the roots are:
[tex]\[ x = 7 \quad \text{and} \quad x = -4. \][/tex]
3. Analyze the intervals determined by the roots: The roots [tex]\(x = 7\)[/tex] and [tex]\(x = -4\)[/tex] divide the real number line into three intervals:
- [tex]\( (-\infty, -4) \)[/tex]
- [tex]\( [-4, 7] \)[/tex]
- [tex]\( (7, \infty) \)[/tex]
We will test the sign of [tex]\(x^2 - 3x - 28\)[/tex] in each of these intervals to see where the quadratic expression is greater than or equal to zero.
4. Test intervals:
- For the interval [tex]\( (-\infty, -4) \)[/tex]:
- Choose a test point [tex]\(x = -5\)[/tex]:
[tex]\[ (-5)^2 - 3(-5) - 28 = 25 + 15 - 28 = 12 \quad (\geq 0). \][/tex]
- For the interval [tex]\( (-4, 7) \)[/tex]:
- Choose a test point [tex]\(x = 0\)[/tex]:
[tex]\[ 0^2 - 3(0) - 28 = -28 \quad (< 0). \][/tex]
- For the interval [tex]\( (7, \infty) \)[/tex]:
- Choose a test point [tex]\(x = 8\)[/tex]:
[tex]\[ 8^2 - 3(8) - 28 = 64 - 24 - 28 = 12 \quad (\geq 0). \][/tex]
It's also important to verify the values at [tex]\(x = -4\)[/tex] and [tex]\(x = 7\)[/tex]:
- At [tex]\(x = -4\)[/tex]:
[tex]\[ (-4)^2 - 3(-4) - 28 = 16 + 12 - 28 = 0 \quad (\geq 0). \][/tex]
- At [tex]\(x = 7\)[/tex]:
[tex]\[ 7^2 - 3(7) - 28 = 49 - 21 - 28 = 0 \quad (\geq 0). \][/tex]
5. Combine the results: From the test points, we observe that the quadratic expression [tex]\(x^2 - 3x - 28\)[/tex] is greater than or equal to zero in the intervals [tex]\((-\infty, -4]\)[/tex] and [tex]\([7, \infty)\)[/tex].
The solution to the inequality [tex]\(x^2 - 3x - 28 \geq 0\)[/tex] is:
[tex]\[ (-\infty, -4] \cup [7, \infty). \][/tex]
Therefore, the correct answer is:
[tex]\[ (-\infty, -4] \text{ or } [7, \infty). \][/tex]
1. Identify the quadratic equation: We start with the quadratic expression given in the inequality:
[tex]\[ x^2 - 3x - 28 \geq 0. \][/tex]
2. Find the roots of the quadratic equation: The next step is to find the roots of the quadratic equation by setting it equal to zero:
[tex]\[ x^2 - 3x - 28 = 0. \][/tex]
To factorize this equation, we look for two numbers that multiply to [tex]\(-28\)[/tex] and add up to [tex]\(-3\)[/tex]. The numbers [tex]\(-7\)[/tex] and [tex]\(4\)[/tex] satisfy these conditions:
[tex]\[ (x - 7)(x + 4) = 0. \][/tex]
So, the roots are:
[tex]\[ x = 7 \quad \text{and} \quad x = -4. \][/tex]
3. Analyze the intervals determined by the roots: The roots [tex]\(x = 7\)[/tex] and [tex]\(x = -4\)[/tex] divide the real number line into three intervals:
- [tex]\( (-\infty, -4) \)[/tex]
- [tex]\( [-4, 7] \)[/tex]
- [tex]\( (7, \infty) \)[/tex]
We will test the sign of [tex]\(x^2 - 3x - 28\)[/tex] in each of these intervals to see where the quadratic expression is greater than or equal to zero.
4. Test intervals:
- For the interval [tex]\( (-\infty, -4) \)[/tex]:
- Choose a test point [tex]\(x = -5\)[/tex]:
[tex]\[ (-5)^2 - 3(-5) - 28 = 25 + 15 - 28 = 12 \quad (\geq 0). \][/tex]
- For the interval [tex]\( (-4, 7) \)[/tex]:
- Choose a test point [tex]\(x = 0\)[/tex]:
[tex]\[ 0^2 - 3(0) - 28 = -28 \quad (< 0). \][/tex]
- For the interval [tex]\( (7, \infty) \)[/tex]:
- Choose a test point [tex]\(x = 8\)[/tex]:
[tex]\[ 8^2 - 3(8) - 28 = 64 - 24 - 28 = 12 \quad (\geq 0). \][/tex]
It's also important to verify the values at [tex]\(x = -4\)[/tex] and [tex]\(x = 7\)[/tex]:
- At [tex]\(x = -4\)[/tex]:
[tex]\[ (-4)^2 - 3(-4) - 28 = 16 + 12 - 28 = 0 \quad (\geq 0). \][/tex]
- At [tex]\(x = 7\)[/tex]:
[tex]\[ 7^2 - 3(7) - 28 = 49 - 21 - 28 = 0 \quad (\geq 0). \][/tex]
5. Combine the results: From the test points, we observe that the quadratic expression [tex]\(x^2 - 3x - 28\)[/tex] is greater than or equal to zero in the intervals [tex]\((-\infty, -4]\)[/tex] and [tex]\([7, \infty)\)[/tex].
The solution to the inequality [tex]\(x^2 - 3x - 28 \geq 0\)[/tex] is:
[tex]\[ (-\infty, -4] \cup [7, \infty). \][/tex]
Therefore, the correct answer is:
[tex]\[ (-\infty, -4] \text{ or } [7, \infty). \][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.